Water soluble, multifunctional antibody-porphyrin gold nanoparticles for targeted photodynamic therapy - Penon, Oriol; Marín, María J.; Russell, David A.; Pérez-García, Lluïsa (Elsevier, 2017)
Photodynamic therapy (PDT) is a treatment of cancer by which tumour cells are destroyed using reactive oxygen species produced by photosensitizers following activation with visible or near infrared light. Successful PDT depends on the solubility and the targeting ability of the photosensitizers. In this work, the synthesis of a porphyrin-based water soluble nanoparticle conjugate containing a targeting agent that recognizes the erbB2 receptor overexpressed on the surface of particular cancer cells is reported. The nanoparticle conjugates were synthesized following two different protocols, viz. a biphasic and a monophasic method, with the aim to determine which method yielded the optimal nanosystem for potential PDT applications. The nanoparticles were characterized using UV–Vis absorption and fluorescence spectroscopies together with transmission electron microscopy and zeta potential measurements; and their ability to produce singlet oxygen following irradiation was investigated following the decay in absorption of a singlet oxygen probe. The nanoparticles synthesized using the monophasic method were shown to produce the highest amount of singlet oxygen and were further functionalized with anti-erbB2 antibody to target the erbB2 receptors expressed on the surface of SK-BR-3 human breast cancer cells. The water soluble, antibody-porphyrin nanoparticle conjugates were shown to elicit targeted PDT of the breast cancer cells.